Isolation and structural characterization of phenolic glycoside and triterpenes in Celastrus hindsii Benth - Sung và cộng sự, Trần Văn (Vietnam Journal of Chemistry, 2014)
Chemical investigation of Celastrus hindsii growing in Quang Binh, Vietnam led to the isolation and structural elucidation of glucosyringic acid, lup-20(29)-ene-3b,11b-diol, lup-20(29)-ene-3-one (lupenone) and lup-5,20(29)-diene-3-one. Their structures were determined on the basis of MS, NMR spectra and comparison with reported data.